Consensus and clinical recommendations for nutritional intervention for head and neck cancer patients undergoing chemoradiotherapy in Taiwan. (June 2018) - Lin, Mei-Chun; Shueng, Pei-Wei; Chang, Wei-Kuo; Mu-Hsin Chang, Peter; Feng, Hsin-Chun; Yang, Muh-Hwa; Lou, Pei-Jen
Highlights: Significant weight loss before treatment predicts poor clinical outcomes. PG-SGA is a common method to define the nutritional status. Nutritional interventions significantly improve clinical outcomes. Omega 3, arginine, EPA, and glutamine may improve the patients' nutritional status. Swallowing training helps to maintain or improve swallowing function. Abstract: Because of the anatomical location, patients with head and neck cancer (HNC) frequently experience dysphagia and malnutrition at the time of diagnosis and these conditions are often exacerbated after chemoradiotherapy. There is an emerging medical need to establish a consensus on nutritional intervention for these patients. A panel of 30 senior physicians and experts from multidisciplinary teams drafted clinical recommendations to improve the management of nutritional interventions in Taiwan and to provide updated treatment strategy recommendations in hope of improving the nutritional status of patients with HNC. This clinical review describes the resulting consensus document, including the impact of malnutrition on clinical outcomes, the role of prophylactic tube feeding, the choice of tube feeding, and the benefit of oral nutritional supplements in patients with HNC undergoing chemoradiotherapy. The outcomes of this review will support clinicians in their efforts to improve the nutritional status of patients with HNC.